Considerations of Physical Design and Implementation for 5 MHz-100 W LLC Resonant DC-DC Converters - Akinori Hariya; Ken Matsuura; Hiroshige Yanagi; Satoshi Tomioka; Yoichi Ishizuka; Tamotsu Ninomiya (Active and Passive Electronic Components)
Recently, high power-density, high power-efficiency, and wide regulation range isolated DC-DC converters have been required. This paper presents considerations of physical design and implementation for wide regulation range MHz-level LLC resonant DC-DC converters. The circuit parameters are designed with 3–5 MHz-level switching frequency. Also, the physical parameters and the size of the planar transformer are optimized by using derived equations and finite element method (FEM) with Maxwell 3D. Some experiments are done with prototype LLC resonant DC-DC converter using gallium nitride high electron mobility transistors (GaN-HEMTs); the input voltage is 42–53 V, the reference output voltage is 12 V, the load current is 8 A, the maximum switching frequency is about 5 MHz, the total volume of the circuit is 4.1 cm3, and the power density of the prototype converter is 24.4 W/cc.